Effect of Newcastle Disease Virus AF2240 on Allografted 4T1 Breast Cancer Cells in Balb/c Mice - Swaminathan, Setareh (2010)
This study was carried out to observe the antitumor effect of NDV AF2240 in vivo using mouse 4T1 breast cancer cell line. One hundred and twenty female mice were assigned randomly into ten groups; negative control (CC), cancer treated with 0.5 μg/mL tamoxifen citrate (CT), cancer treated with NDV titre 8HA (CNDV8), NDV 16HA (CNDV16), NDV 32HA (CNDV32), NDV 64HA (CNDV64), combination of NDV 8HA+tamoxifen (CNDV8+T), NDV 16HA+tamoxifen (CNDV16+T), NDV 32HA+tamoxifen (CNDV32+T) and NDV 64HA+tamoxifen (CNDV64+T). These mice were induced with 4T1 cells and treatments were started concurrently and given daily for a month. Forty eight mice with tumour growth were euthanized weekly to remove tumour samples. At the end of the experiment, microscopic examinations were done on the cross-sections of tumour samples of these mice. Tumour growth was observed in groups; CC, CT, CNDV32+T and CNDV64+T, whereas, the rest of the groups had no tumour growth. CNDV32+T and CNDV64+T groups did not show any tumour regression, having a very low apoptotic index (AI) and a high mitotic index (MI) throughout the one month treatment indicating that these treatments were not therapeutic. TUNEL assay was carried out to quantify apoptotic cells and the findings were concurrent with the AI results, where only CT group had an increase in apoptotic cells when compared at week 1 to week 4. Tamoxifen alone was able to regress the tumour but not with a significant difference. Tumours with an inactivated tumour suppressor gene, p53, produced p53 mutant proteins. Results showed that there was a strong direct correlation between the amount of mutant protein present in the nucleus of cancer cells in CC, CT, CNDV32+T and CNDV64+T groups with the MI score. Mutated p53 proteins were not able to inhibit growth of cancer cells, leading to high mitotic activity and increase in cell proliferation. In groups CNDV32+T and CNDV64+T, there was evidence that NDV caused cytoplasmic sequestration of p53 protein from the nucleus to the cytoplasm, indicating the enhancement by the virus to induce apoptosis on these cells. The breast tissues of CNDV8, CNDV16, CNDV32, CNDV64, CNDV8+T and CNDV16+T groups which had no tumour were also stained to detect localization of p53. It was found highly expressed in the cytoplasm of ductal epithelium similar to quiescent mammary glands, denoting these groups were tumour free. The findings of this study suggest NDV titres 8, 16, 32 and 64HA inhibit the growth of 4T1 cells, preventing tumour formation. Not all the combinations of NDV and tamoxifen were effective, the higher NDV titres combined with tamoxifen were neither able to inhibit nor regress tumour growth. In summary, NDV AF2240 alone can inhibit growth of 4T1 cancer cells and, thus, can be used as a potential oncolytic agent for breast cancer treatments. NDV is significantly more effective than tamoxifen and can be a very useful alternative anticancer agent for breast tumours.